Do Patents Lead to an Increase in Firm Value? Evidence from Korea - Jangwook Lee (KDI Journal of Economic Policy, 2020)
Patents are widely used in the literature as a measure of firm-level innovation. It is regarded that patents improve a firm's operational environment and ultimately increase the value of the firm. However, the relationship between patents and firm value in Korea is under-explored in the literature due to the difficulty of constructing datasets. This paper examines whether patents in Korea increase the market value of a firm. To do this, I exploit novel data on firm-level patents and financial information of all listed Korean companies during the period of 1993- 2015 and estimate the non-linear production-function type of Tobin's q equations on R&D, patents, and citations. Surprisingly, I find that patents and citations are weakly associated with firm value, while R&D is strongly associated with an increase in firm value. These results direct imply that policymakers in Korea should enhance patenting incentives to encourage firms to innovate.
Keywords: O30; O32; O34; 330; Innovation; Firm Value; Tobin's q; R&D; Patent